2013
DOI: 10.4049/jimmunol.1202959
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Vδ2+ T Cells Populate the Human Intestinal Mucosa and Enhance IFN-γ Production by Colonic αβ T Cells

Abstract: In nonhuman primates, Vγ9Vδ2+ (Vδ2)T cells proliferate and accumulate in mucosal tissues following microbial activation. Human Vδ2T cells produce proinflammatory cytokines in response to bacterial species that colonize the gut, but the role played by Vδ2T cells in intestinal immunity is unknown. We hypothesized that circulating Vδ2T cells can populate the human intestine and contribute to mucosal inflammation. Cell suspensions prepared from peripheral blood and intestinal biopsies were stimulated with microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 60 publications
3
47
0
Order By: Relevance
“…These data indicate a potential role for Vδ2 T cells in the pathology of Crohn's disease (CD), which is characterized by enhanced effector function of CD4 + T cells directed against components of the gut microbiota. In addition to our own detection of Vδ2 T cells in human colonic lamina propria in situ (11), these cells have also been observed in gastrointestinal lymphoid tissues (12) and were previously identified in the gut in a small number of CD patients (13,14), but the role played by these cells in mucosal inflammation in CD is currently unknown.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…These data indicate a potential role for Vδ2 T cells in the pathology of Crohn's disease (CD), which is characterized by enhanced effector function of CD4 + T cells directed against components of the gut microbiota. In addition to our own detection of Vδ2 T cells in human colonic lamina propria in situ (11), these cells have also been observed in gastrointestinal lymphoid tissues (12) and were previously identified in the gut in a small number of CD patients (13,14), but the role played by these cells in mucosal inflammation in CD is currently unknown.…”
Section: Introductionmentioning
confidence: 61%
“…Vδ2 T cells are unconventional blood lymphocytes that are uniquely able to recognize PAg produced by tumor cells and microbes (1,5,6). We recently demonstrated that PAg exposure stimulates human blood Vδ2 T cells to upregulate the gut-homing integrin α4β7 and increase binding to the intestinal addressin MAdCAM-1 (11). To test the hypothesis that human Vδ2 T cells contribute to mucosal inflammation in CD, we first used flow-cytometry to assess the gut-homing potential of blood Vδ2 T cells in a cohort of CD patients who had moderately active disease but who were not receiving immunosuppressive therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a flip side of the potential benefit of the adjuvant properties of Vc9/Vd2 T cells, a dysregulated generation of APCs under the influence of Vc9/Vd2 T cells may eventually result in uncontrolled inflammation and the generation of cellular and humoral autoimmune responses, thereby contributing to the clinical symptoms in scenarios such as psoriasis [226], inflammatory bowel disease [227], celiac disease [196,228], and multiple sclerosis [229]. More research is clearly needed to delineate the complex interactions of Vc9/Vd2 T cells (and other unconventional T cells) with different immune and non-immune cells, both locally and systemically, and define how such knowledge can be exploited for therapeutic interventions to either boost protective immune responses or suppress excessive inflammation.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…This provides further evidence that RA can have direct and indirect effects on CD4 + effector T cells. Studies in humans (84) showed that the RA-RARa pathway induces expression of the gut-homing integrin a4b7 and its ligand addressin (MAdCAM-1) on circulating Vd2…”
Section: Impact Of Ra On Gd T Cells Nk Cells and Innate Lymphoid Cellsmentioning
confidence: 99%